2017
DOI: 10.1159/000479724
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of MicroRNAs in the Inner Ear of Elderly People by Real-Time PCR Quantification

Abstract: The molecular mechanisms underlying age-related hearing loss are unknown, and currently, there is no treatment for this condition. Recent studies have shown that microRNAs (miRNAs) and age-related diseases are intimately linked, suggesting that some miRNAs may present attractive therapeutic targets. In this study, we obtained 8 human temporal bones from 8 elderly subjects at brain autopsy in order to investigate the expression profile of miRNAs in the inner ear with miRNA arrays. A mean of 478 different miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Two were animal studies, 16,17 four included findings from animal cell culture studies, 1821 one comprised findings from animal and human subjects, 13 and two concerned findings from human subjects alone. 22,23…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two were animal studies, 16,17 four included findings from animal cell culture studies, 1821 one comprised findings from animal and human subjects, 13 and two concerned findings from human subjects alone. 22,23…”
Section: Resultsmentioning
confidence: 99%
“…With ageing, more microRNA expression levels are downregulated than upregulated. 16,23 Amongst them are miR-181 and miR-183 family members, which are known mediators of cell proliferation and differentiation pathways. The miR-181 family consists of four members: miR-181a, miR-181b, miR-181c and miR-181d.…”
Section: Resultsmentioning
confidence: 99%
“…32 Until now, accumulating evidence indicates that miRNAs serve essential roles on the maintenance of inner ear function. 33 GeneChip miRNA microarray and real-time PCR were used to examine the samples from C57 and CBA mice, and the results suggested that 182 miRNAs were differentially expressed. 34 Furthermore, Sekine et al suggested that the expression of 348 miRNAs was detected in human temporal bones; 277 miRNAs were downregulated and 71 miRNAS were upregulated during aging.…”
Section: Cimirnas In Arhlmentioning
confidence: 99%
“…74 MiR-451a is a member of the miR-451 family. 75 MiR-451 is expressed in human cochlea 33 and inner ear perilymph. 40 A previous study revealed the key roles of miR-451 in response to oxidative stress.…”
Section: Cimirnas In Nihlmentioning
confidence: 99%
“…Various studies have demonstrated that miRNA dysregulation is associated with a variety of pathological conditions, including tumors, neurological disorders and other acute and chronic diseases (28)(29)(30)(31). Of note, some studies have also demonstrated that a number of miRNAs are involved in inner ear development, differentiation and the survival of inner ear hair cells, suggesting that changes in their expression levels may play a critical role in the onset of hearing disorders (32)(33)(34)(35). On these bases, the aim of the present review article was to report a summary of the studies that have been conducted over the past years in order to provide a better understanding of the role of miRNAs in inner ear development.…”
Section: Role Of Micrornas As Novel Diagnostic Biomarkers and Potenti...mentioning
confidence: 99%